Comparison of Copper, Iron, Iodine, Rubidium, Strontium and Zinc contents in Thyroid Tissue adjacent to Thyroid Malignant and Benign Nodules - Zaichick, Vladimir (British Journal of Healthcare and Medical Research, 2022)
Objective: Thyroid nodules (TN) are the most common endocrine disorder worldwide. Etiology and pathogenesis of thyroid benign and malignant nodules (TBN and TMN, respectively) are still not enough understood. The present study was performed to clarify the role of some trace elements (TEs) in the origination and development of TN. Methods: Thyroid tissue levels of copper (Cu), iron (Fe), iodine (I), rubidium (Rb), strontium (Sr), and zinc (Zn) were prospectively evaluated in thyroid tissue adjacent to TBN (79 patients) and to TMN (41 patients). Measurements were performed using a combination of non-destructive 109Cd and 241Am radionuclide-induced energy-dispersive X-ray fluorescent analysis. Results of the study were additionally compared with previously obtained data for the same TEs in “normal” thyroid tissue. Results: I was observed that in thyroid tissue adjacent to TMN the mass fractions of I and Rb were 1.53 and 1.79 times, respectively, higher than those in thyroid tissue adjacent to TBN. The common characteristics of thyroid tissue adjacent to TBN and TMN were similar contents of Fe, Sr, and Zn , as well as elevated levels of Cu, I, and Rb, which overdrew those in “normal” thyroid approximately in 2.2, 1.4, and 1.6 times, respectively. Conclusions: Role of TEs in etiology and pathogenesis TBN and TMN is similar and exessive accumulation of Cu, I, and Rb in thyroid tissue may be involved in the TN origination and development.